2013
DOI: 10.1186/1559-4106-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane topology analysis by RICM enables marker-free adhesion strength quantification

Abstract: Reflection interference contrast microscopy (RICM) allows the visualization of the cell's adhesion topology on substrates. Here it is applied as a new label-free method to measure adhesion forces between tumor cells and their substrate without any external manipulation, i.e., the application of force or adjustments in the substrate elasticity. Malignant cancer transformation is closely associated with the down-regulation of adhesion proteins and the consequent reduction of adhesion forces. By analyzing the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Indeed, these adhesive areas appear as dark patches in IRM images taken in the in-plane mode (18,22,23). By monitoring the evolution of these adhesive areas over the duration of a complete detachment event, we found that the detachment does not occur by peeling from the periphery but rather appears to be initiated in the region directly under the micropipette, see Movie S2 and Fig.…”
Section: Detachment Force and Geometric Parametersmentioning
confidence: 93%
See 4 more Smart Citations
“…Indeed, these adhesive areas appear as dark patches in IRM images taken in the in-plane mode (18,22,23). By monitoring the evolution of these adhesive areas over the duration of a complete detachment event, we found that the detachment does not occur by peeling from the periphery but rather appears to be initiated in the region directly under the micropipette, see Movie S2 and Fig.…”
Section: Detachment Force and Geometric Parametersmentioning
confidence: 93%
“…(B) Plot of the experimental intensity extrema positions versus the predictions from Eq. 1 (18,22), for l ¼ 340 nm. The good fit for this value of l is evidenced by the slope of the linear regression: 1.003 5 0.007.…”
Section: Detachment Force and Geometric Parametersmentioning
confidence: 99%
See 3 more Smart Citations